Effects of high-intensity interval training on platelet function in cardiac rehabilitation: a randomised controlled trial. Issue 1 (17th July 2019) - Heber, Stefan; Fischer, Beatrix; Sallaberger-Lehner, Marina; Hausharter, Maria; Ocenasek, Helmuth; Gleiss, Andreas; Fischer, Michael J M; Pokan, Rochus; Assinger, Alice; Volf, Ivo
Abstract : Objective: To compare effects of moderate-intensity continuous training (MICT) and high-intensity interval training (HIIT) on platelet function in patients undergoing cardiac rehabilitation, as hyper-reactive platelets are involved in atherogenesis and atherothrombosis. Methods: In this single-centre parallel group randomised controlled trial, male patients after an acute coronary syndrome under dual antiplatelet therapy performed MICT or HIIT+MICT for 12 weeks. Main outcome was platelet reactivity measured by the half-maximal concentration (EC50 ) of platelet agonist thrombin receptor-activating peptide-6 (TRAP-6) in terms of P-selectin expression. EC50 was determined at baseline, after 6 and 12 weeks, each time at physical rest and on exertion. Results: 82 patients were randomised to MICT or HIIT+MICT. Mean (95% CI) baseline EC50 values at physical rest were 6.7 µM (6.3 µM to 7.0 µM) TRAP-6. After 6/12 weeks, 36/33 MICT and 34/28 HIIT+MICT patients were examined. HIIT+MICT patients had 0.9 µM (0.4 µM to 1.4 µM)/0.5 µM (−0.1 µM to 1.0 µM) higher EC50 values than MICT ones, and the propensity of their platelets to form aggregates with monocytes was significantly lower after 12 weeks. Short-term strenuous physical exertion was generally associated with platelet activation and an EC50 reduction of 0.7 µM (0.6 µM to 0.8 µM). HIIT+MICT patients tended to be fitter after 12 weeks. No serious harms were observed. Conclusions: Including HIIT in cardiac rehabilitation seems to confer additional benefits compared with MICT alone, which should be confirmed in clinical trials with hard endpoints. Exertion-induced platelet activation and hyper-reactivity occur despite dual antiplatelet therapy. Trial registration number: NCT02930330 ; Results.